2015
DOI: 10.32800/abc.2015.38.0207
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing butterfly abundance after a severe wildfire in Mediterranean vegetation

Abstract: Despite the attention given to the ecology of butterflies, little is known about their community response to wildfires in the Mediterranean region. Here, we evaluated the butterfly assemblage two years after a severe, 13,000 ha wildfire in Catalonia (NE Spain) in relation to the surrounding unburned habitat. Using visual transect censuses we assessed community parameters such as abundance, diversity, species richness and equitability in burned and unburned areas. Correspondence analysis was used to analyse spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The second site at Yawmatwa CREMA (YS2) was the most even (J' = 0.936) in terms of species distribution. (Larsen 1994(Larsen , 2006 Butterfly assemblage in an area is determined by vegetation cover and diversity of the vegetation present (Addo-Fordjour et al 2015;Kyerematen et al 2018;Serrat et al 2015;Ubach et al 2020). The ongoing initiative by the Netherlands Development Organization (SNV), to practice the Shaded Cocoa Agroforestry (SCAF), has provided vegetation cover and protected the habitats of species in these areas which probably has accounted for the high diversity of butterfly species here.…”
Section: Resultsmentioning
confidence: 99%
“…The second site at Yawmatwa CREMA (YS2) was the most even (J' = 0.936) in terms of species distribution. (Larsen 1994(Larsen , 2006 Butterfly assemblage in an area is determined by vegetation cover and diversity of the vegetation present (Addo-Fordjour et al 2015;Kyerematen et al 2018;Serrat et al 2015;Ubach et al 2020). The ongoing initiative by the Netherlands Development Organization (SNV), to practice the Shaded Cocoa Agroforestry (SCAF), has provided vegetation cover and protected the habitats of species in these areas which probably has accounted for the high diversity of butterfly species here.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, our results align with butterfly DSS scores (Nelson and Andersen 1994, 1999), suggesting that sites burned at least 4 years before our surveys supported the highest diversity and abundance of disturbance‐sensitive butterfly species, such as the queen, the fatal metalmark, and the sleepy orange. In some xeric systems, butterfly community recovery after a burn can occur more rapidly (Serrat et al 2015) in response to the openness of treated habitat even before herbaceous plants and nectar resources are fully established (Waltz and Covington 2004). In our desert riparian system, our results suggested that butterfly habitat requires several years of recovery, which might especially be true in areas where herbicide applications were used, which was the case at our managed study sites (Briggs et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To date, space‐for‐time substitution surveys have identified pollinator responses to different fire intervals. For example, butterfly communities in southern France recovered within 2 years post‐fire (Serrat et al, 2015 and refs. therein).…”
Section: Stressors On P–p Communitiesmentioning
confidence: 99%
“…Numa et al, 2008). This focus on butterflies may reflect (i) their charismatic status, and/or (ii) their value as indicators of environmental change (Serrat et al, 2015). Finally, although vertebrate pollination occurs regularly (at least outside the Mediterranean Basin), bird or mammal pollinators are rarely co-considered in p-p community surveys (Supporting Information).…”
Section: Taxonomic Biasesmentioning
confidence: 99%